Bioaccumulation of heavy metals in some shell fishes and soil from polluted in chaktai khal of karnafully River, Chittagong (Bangladesh Journal of Zoology, 2015)
Abstract not availableBangladesh J. Zool. 43(1): 145-151, 2015